Details of left ventricular radial wall motion supporting the ventricular theory of the third heart sound obtained by cardiac MR - Codreanu, I; Robson, M; Rider, O; Pegg, T; Dasanu, C; Jung, B; Rotaru, N; Clarke, K; Holloway, C (British Institute of Radiology, 2014)
OBJECTIVE: Obtaining new details of radial motion of left ventricular (LV) segments using velocity-encoding cardiac MRI. METHODS: Cardiac MR examinations were performed on 14 healthy volunteers aged between 19 and 26 years. Cine images for navigator-gated phase contrast velocity mapping were acquired using a black blood segmented κ-space spoiled gradient echo sequence with a temporal resolution of 13.8 ms. Peak systolic and diastolic radial velocities as well as radial velocity curves were obtained for 16 ventricular segments. RESULTS: Significant differences among peak radial velocities of basal and mid-ventricular segments have been recorded. Particular patterns of segmental radial velocity curves were also noted. An additional wave of outward radial movement during the phase of rapid ventricular filling, corresponding to the expected timing of the third heart sound, appeared of particular interest. CONCLUSION: The technique has allowed visualization of new details of LV radial wall motion. In particular, higher peak systolic radial velocities of anterior and inferior segments are suggestive of a relatively higher dynamics of anteroposterior vs lateral radial motion in systole. Specific patterns of radial motion of other LV segments may provide additional insights into LV mechanics. ADVANCES IN KNOWLEDGE: The outward radial movement of LV segments impacted by the blood flow during rapid ventricular filling provides a potential substrate for the third heart sound. A biphasic radial expansion of the basal anteroseptal segment in early diastole is likely to be related to the simultaneous longitudinal LV displacement by the stretched great vessels following repolarization and their close apposition to this segment.